Analytical Evaluation of Solder Stress in Electronic Packages Subjected to Random Vibrations - Gharaibeh, Belal (2023)
Electronic components, during assembly, transportation, and operation, are exposed to a diverse array of dynamic loads, encompassing high and low frequency vibrations, shock, impact, and most importantly, random vibrations. Such rigorous loading conditions necessitate the design of electronic components that can endure these harsh circumstances. Analytical methods, owing to their cost-effectiveness, are predominantly employed to investigate the longevity and resilience of these electronic structures, circumventing the need for protracted and costly experiments. In this study, an analytical discussion is presented concerning the random vibration loads applied to printed circuit boards (PCBs) fitted with surface-mounted components. The electronic package is modelled using the multi-layer plate theory, where the board, solder layer, and component are all conceptualized as elastic rectangular plates. The ensuing stress and potential failure of solder joint layers due to the random vibration loading are scrutinized, alongside an examination of how problem parameters, such as the width of the board and the imposed boundary conditions, impact the stress values within the solder joints. The results derived from the analytical solution reveal that solder stresses induced by random vibrations are diminished in shorter joints, enhancing their reliability. The findings of this research corroborate the results obtained from finite element modelling, thereby validating the analytical approach.